The Effect of Farm Credits on Crop Production In Jambalul, Afgoia –Somalia - Abdulkadir, Mohamed Osman; Hassan, Mohamed Mohamud; Ahmed, Abdirahman Mohamed; Omar, Shire Hassan (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2017)
Farm credit plays a pivotal role in agrarian and rural development as it allows farmers gain economies of scale, venture into new fields of production, engage new technologies and enable them to provide utilities for a broadening market so this paper aims to examine the effects of farm credits on crop production in Jambalul, Afgoia and to find out the magnitude of the farm credit services with the findings in Jambalul, Afgoia, and Lower Shebelle in Somalia. A survey research method has been adopted to examine the effects of farm credits on crop production in Jambalul, Afgoia. The data were collected through questionnaires filled by the respondents and the survey respondents were asked to rate eighteen questions developed from the three objectives of the study. The results indicated that farm credits is an important tool for the production of crops through providing of loans and setting stable rural economic community. Farm credits improve the living standard of farmers by increasing their yielding and reducing the poverty.